Análisis espacial y patrones de asentamiento en el bajo río San Jorge (Caribe colombiano) (2010)
ABSTRACT: In this paper asks how places were distributed living spaces, fields for agriculture and hydraulic control in the old course of the lower river San Jorge (Colombian Caribbean), The spatial analysis allows determine the concentration, dispersion and association of the different elements found in the anthropogenic landscape.